The Meaning and Classification of Financial and Administrative Deviations according to the Thought of CSR: An Initiative to Promote Contemporary Internal Auditing Idea - Younis A. Battal Saleh (Entrepreneurship Faculty, Universitas Garut, 2022)
Abstract – This theoretical study aims to classify administrative and financial deviations in accordance with the content of the idea of CSR.. The approach used in this study is creative; creative thinking is the ability to generate a new and useful idea that has not been touched before; a skill that enables you to create original, unique, and unconventional ideas. The researcher adopted the idea of classification based on affiliation. Commitment to CSR is essentially a commitment to the four responsibilities ″economic, legal, ethical, and philanthropic.″ Also, administrative and financial deviations are violations that can be classified within one of the following areas: economic, legal, ethical, or philanthropic, if the reluctance to do charitable work is considered a deviation. Therefore, any administrative or financial deviations can be attributed to one of those responsibilities. More profoundly and extensively, this study was able to classify administrative and financial deviations according to the thought of CSR into four categories: Deviation from economic responsibility; deviation from legal responsibility; deviation from ethical responsibility; deviation from philanthropic responsibility. Classifying administrative and financial deviations according to the thought of CSR is to enrich and enhance the idea of contemporary internal auditing- which has become concerned with matters of CSR. According to the modern perception regarding internal audit functions, the internal audit department in any organization can adopt and use this classification, whether in the field of ensuring CSR reports, monitoring and evaluating CSR, or reporting on CSR. Adopting this classification will help internal audit departments accomplish their tasks in the field of CSR in a more accurate and objective manner.